2012
DOI: 10.1111/j.1542-4758.2012.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐grafted dialysis membrane allows minimal systemic anticoagulation in regular hemodialysis patients: A prospective proof‐of‐concept study

Abstract: This prospective, multicenter, proof-of-concept study aimed to evaluate the possibility to reduce the ordinary heparin dose and the systemic anti-Xa activity during hemodialysis (HD) sessions using a new heparin-grafted HD membrane. In 45 stable HD patients, the use of a heparin-grafted membrane with the ordinary heparin dose was followed by a stepwise weekly reduction of dose. Reduction was stopped when early signs of clotting (venous pressure, quality of rinse-back) occurred during two out of three weekly HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
(56 reference statements)
0
28
0
1
Order By: Relevance
“…The use of heparin pregrafted membranes increases the rate of successful heparin-free intermittent hemodialysis sessions in high bleeding risk patients [60] and allows for a reduction of systemic heparin dosing, without compromising the dialysis session [61]. However, none of the published studies assessing the oXiris ® membrane has specifically evaluated its antithrombogenic properties in the setting of acute septic patients and CRRT.…”
Section: Antithrombogenic Treatmentmentioning
confidence: 99%
“…The use of heparin pregrafted membranes increases the rate of successful heparin-free intermittent hemodialysis sessions in high bleeding risk patients [60] and allows for a reduction of systemic heparin dosing, without compromising the dialysis session [61]. However, none of the published studies assessing the oXiris ® membrane has specifically evaluated its antithrombogenic properties in the setting of acute septic patients and CRRT.…”
Section: Antithrombogenic Treatmentmentioning
confidence: 99%
“…In vitro and in vivo data requested for CE marking (conformity with European Medical Device Directive 93/42/ EEC) have shown the stability of heparin grafting with absolutely no release (Supplementary Appendix online). In a study conducted in 45 regular dialysis patients, Kessler et al 15 found that the systemic heparin dose could be reduced by 45±13% without any coagulation issues. In addition, Sanchez-Canel et al 16 have observed, in six patients treated with postdilution hemodiafiltration, no increase in complete clotting event frequency with HGM without systemic anticoagulation, compared with polysulfone membrane and standard anticoagulation with nadroparin.…”
mentioning
confidence: 99%
“…A significant reduction in heparin dose and anti-Xa activity at the end of HD sessions was possible in stable HD patients using heparin-grafted membranes [22]. This method could be used to reduce the risk of bleeding and other adverse heparin events.…”
Section: Discussionmentioning
confidence: 99%